Antibacterial efficacy of sodium hypochlorite versus apple cider vinegar against Enterococcus faecalis in contracted endodontic cavity: An in vitro study - Kaur Supreet; Karkala Venkappa Kishan; Nimisha Chinmay Shah (Endodontology, 2022)
Aim: The aim of this study is to evaluate and compare the antibacterial efficacy of 3% sodium hypochlorite with 5% apple cider vinegar using passive ultrasonic irrigation (PUI) against Enterococcus faecalis in contracted endodontic access cavity on mandibular molars. Methods: Contracted access cavity was prepared in 30 extracted human permanent mandibular molar teeth. The root canals were incubated with strain of E. faecalis MTCC 9845 (Strain designation – HBL/BAC– 002/08–09) using 15 K-type manual file for 3 weeks. At this point, the S1 sample was collected using 15 paper points. The extracted teeth were randomly divided into two groups: sodium hypochlorite group and apple cider vinegar group. After mechanical instrumentation up to 25/04 rotary files HyFlex CM (Coltene Whaledent, Altstätten, Switzerland) and use of respective irrigants (3% sodium hypochlorite and 5% apple cider vinegar) using PUI, S2 sample was collected using 25 size paper point. The cultivated samples were incubated at 37°C for 24 h, and the number of bacterial colonies was counted as colony-forming units (CFUs)/mL. Data obtained from S1 and S2 were tabulated and subjected to Wilcoxon signed-ranks test and Mann–Whitney test. Results: There was a significant reduction in microbial count in both groups (P < 0.05) when preoperative CFUs were compared with postoperative. There was slightly higher reduction in the apple cider vinegar group in S2 sample, as compared to the sodium hypochlorite group, but it was not statistically significant (P > 0.05). Conclusion: Antimicrobial activity of 5% apple cider vinegar is similar to 3% sodium hypochlorite.